Pelvic Inflammatory Disease in the Form of Peritoneal Abscess Complicating Late Pregnancy - H. Mahesha Navada; B. Poornima Ramachandra Bhat (Case Reports in Obstetrics and Gynecology)
Chronic pelvic inflammatory disease (PID) in the form of peritoneal abscess during pregnancy is almost unheard entity. Early and antenatal diagnosis may be difficult or may be revealed only during caesarean section. We report a case of peritoneal abscess secondary to pelvic inflammatory disease incidentally found at repeat caesarean section. It was managed by conservative surgical approach.